A STUDY OF MUSIC LEARNING ACHIEVEMENT AND RECORDER PLAYING SKILLS THROUGH MUSIC CAMP ACTIVITIES FOR PRIMARY SCHOOL STUDENTS - Saehen, Kananek; Vatanakhiri, Chutima; Koedsuwan, Suphot (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article investigates the learning achievement in music and recorder playing skills through music camp activities for elementary school students. The objectives were: 1) to study the music learning achievement of elementary school students before and after learning using music camp activities, and 2) to study the recorder playing skills of elementary school students after learning using music camp activities, with a criterion of higher than 70%. This was a quasi-experimental research study conducted in five steps: Step 1: Define the objectives and topic of the research; Step 2: Study relevant research content; Step 3: Create research instruments; Step 4: Analyze the collected data; Step 5: Conclude and discuss the results. The research findings indicated that: 1) The achievement in music learning for primary school students using music camp activities was significantly higher after learning than before learning at a statistical significance of >.01 2) The recorder playing skills of primary school students using music camp activities after learning were significantly higher than the 70 percent criterion at a statistical significance of >.01